Sensor data collected during the sampling in river Paimionjoki - Samu Elovaara; Lingbin Zhao; Eero Asmala; Hermanni Kaartokallio; David N Thomas (PANGAEA, 2025)
This table contains sensor data collected during the sampling and all measurements that were conducted in the laboratory before any experimental manipulations. During each sampling the in-situ particle size distribution was measured by laser diffraction (data presented in a separate table), and conductivity, dissolved oxygen concentration, pH and temperature were measured using a multiparameter sonde (EXO2, YSI). Laboratory measurements of the collected surface water samples include chromophoric and fluorescent dissolved organic matter, chlorophyll a concentration, suspended particulate matter, particulate organic carbon and dissolved elements.
In: Elovaara, S et al. (2025): Gypsum flocculation experiment in river Paimionjoki, Finland, 2022 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.967477